2020
DOI: 10.1186/s13020-019-0284-3
|View full text |Cite
|
Sign up to set email alerts
|

Luo Tong formula attenuates retinal inflammation in diabetic rats via inhibition of the p38MAPK/NF-κB pathway

Abstract: Background: Diabetic retinopathy (DR) is a serious microvascular complication of diabetes and remains the leading cause of blindness in adults. Retinal inflammation is playing a crucial role in the development of DR, and targeting inflammatory mediators is a promising strategy for controlling DR. Here, we investigated compound Chinese medicine Luo Tong formula (LTF) alleviated retinal inflammatory responses in a STZ-induced diabetic rat model. Methods: Sprague-Dawley rats were divided into four groups: control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…The changes caused by ROS in DR cannot be explained by only a single signaling pathway [ 97 ]. Major signaling pathways contributing to the pathophysiology of DR, in which ROS are involved, are the MAPK pathway, the polyol pathway, the renin-angiotensin system (RAS) pathway, the protein kinase C (PKC) pathway, the PARP pathway and the advanced glycation endproducts (AGEs) pathway [ 98 , 99 , 100 , 101 ].…”
Section: Ros and Drmentioning
confidence: 99%
See 1 more Smart Citation
“…The changes caused by ROS in DR cannot be explained by only a single signaling pathway [ 97 ]. Major signaling pathways contributing to the pathophysiology of DR, in which ROS are involved, are the MAPK pathway, the polyol pathway, the renin-angiotensin system (RAS) pathway, the protein kinase C (PKC) pathway, the PARP pathway and the advanced glycation endproducts (AGEs) pathway [ 98 , 99 , 100 , 101 ].…”
Section: Ros and Drmentioning
confidence: 99%
“…The MAPK pathway is also known to exert positive feedback mechanisms on ROS production in activation of the NF-κB pathway, AP-1, and p53 transcription factors [ 106 , 107 ]. Activation of these transcription factors can induce the expression of genes for a large number of inflammatory mediators [ 99 ]. Based on studies in rat models of DR, it has been suggested that the MAPK may be one of the chronic causes of inflammation and apoptosis in DR [ 107 , 108 ].…”
Section: Ros and Drmentioning
confidence: 99%
“…Luo Tong formula (LTF) originated from Di Dang Decoction ( Synopsis Golden Chamber ), we previously reported that LTF prevented DR in rats. Moreover, we found that it protected endothelial cells by ameliorating inflammation and inhibiting cell apoptosis ( Pang et al, 2020a ; Zhou et al, 2000 ). However, the upstream mechanism involved remains unclear.…”
Section: Introductionmentioning
confidence: 89%
“…The total retinal thickness was measured at 400× magnification; two measurements were taken for each section at the two reference lines, which were 1 mm away from the optic nerve on both the superior and inferior sides. The number of the retinal ganglion cells (RGC) was measured at 400× magnification ( Zhang et al, 2018 ). The thickness of the retinas was measured from the inner limiting membrane to the tips of the photoreceptor outer segments.…”
Section: Methodsmentioning
confidence: 99%
“…HSV-1 also activates the JNK and p38 MAP kinase signaling pathways, which further contribute to cytolytic host cell effects (Zachos et al, 1999;Diao et al, 2005;Hargett et al, 2005). In turn, p38 and JNK are known apoptosis regulators and may be implicated in neurodegeneration and brain and retina neurogenic defects (Shou et al, 2003;Diao et al, 2005;Dhanasekaran and Reddy, 2008;Shklover et al, 2015;Wang et al, 2018;Kawamura and Kano, 2019;Kovacs et al, 2019;Lei et al, 2020;Pang et al, 2020). Although no direct evidence has indicated direct effects of HSV infection to retinal progenitor cells, either in vitro, in vivo or in human cases, it is tempting to assume that, similarly to what is observed in cortical progenitor cells, retinal progenitor cells may be susceptible to HSV infection, resulting in similar neurogenesis and apoptosis effects.…”
Section: Congenital Herpes Simplex Infectionmentioning
confidence: 99%